2022
DOI: 10.1186/s13195-022-01075-8
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on quality of life along the spectrum of Alzheimer’s disease

Abstract: Background Quality of life (QoL) is an important outcome from the perspective of patients and their caregivers, in both dementia and pre-dementia stages. Yet, little is known about the long-term changes in QoL over time. We aimed to compare the trajectories of QoL between amyloid-positive and amyloid-negative SCD or MCI patients and to evaluate QoL trajectories along the Alzheimer’s disease (AD) continuum of cognitively normal to dementia. Methods We included longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(35 reference statements)
4
5
0
Order By: Relevance
“…Furthermore, the occurrence and severity of NPS increased as cognitive decline worsened, while the QoL decreased. These results are in line with previous research findings [ 78 , 79 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, the occurrence and severity of NPS increased as cognitive decline worsened, while the QoL decreased. These results are in line with previous research findings [ 78 , 79 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, unpaid caregivers may jeopardize their own financial security by diverting resources and time away from their own careers and financial well-being. Findings from prior investigations exploring the relationship between AD disease severity and QoL are inconsistent, as evident in the literature [44][45][46][47][48]. Of interest, a multicenter European prospective community-based cohort study of 616 patientcaregiver dyads did not find a significant change in self-reported QoL over time by AD severity for either patients or caregivers [49].…”
Section: Discussionmentioning
confidence: 95%
“…Another consideration is that discordance between clinician's assessments of AD severity and cognitive test-based assessments has been documented and may differ by clinician types [59], thus there may be some variability in MCI and AD severity classifications. We did not require AD biomarker testing, therefore it is possible that some patients in the MCI group had MCI due to causes other than AD; this may impact findings as there is data supporting that amyloid-positive MCI is associated with decreased QoL vs amyloid-negative MCI [45]. Additionally, the DEMQOL-Proxy was used for QoL assessments, and discrepancies between QoL ratings by patients with dementia and their proxies have been well documented, especially with increasing disease severity [60][61][62].…”
Section: Limitationsmentioning
confidence: 99%
“…Patients with symptomatic AD progress from early stages (MCI or MILD AD) to the later stages gradually over a period of years and develop greater symptom severity and dependence on others for care with each stage [4,30]. At present, the focus of AD treatments is shifting from managing symptoms to targeted therapy aimed at slowing the progression of the disease [6].…”
Section: Discussionmentioning
confidence: 99%